THE IMPLEMENTATION OF THEME-BASED TEACHING IN IMPROVING STUDENTS’ GRAMMAR SKILL - Sartika Permata R.P (Journal of English and Education, 2017)
The study entitled “The Implementation of Theme-Based Teaching in Improving Students’ Grammar Skill” was aimed to find out the effectiveness of theme-based teaching in improving students’ grammar skill and the students’ responses toward the treatment. In this study, two different treatments were given to be compared hence quasi-experimental was conducted. The research involves two groups of participants, namely experimental group and control group. Furthermore, pre-test, posttest and questionnaire were chosen as the instruments of the research in gaining the data. The result of the data demonstrated that theme-based teaching was able to exhibit statically significant result toward students’ grammar skill. Moreover, the students’ responses which are collected through the questionnaire revealed positive attitudes. Therefore, the implementation of theme-based teaching is effective in Junior High School especially in improving students’ grammar skill.